Welfare state, social policy and social sustainability, within the context of the permacrisis - Nikos Papadakis; Stylianos Ioannis Tzagkarakis (Frontiers in Political Science)
IntroductionSustainable development is based on three interrelated and equally important pillars; the environmental, the economic and the social. The social pillar involves building a framework that promotes the well-being of the whole population with the ultimate aim of preserving social cohesion, while reducing social discrimination. In our analysis, the concept of social sustainability refers to the need for the creation of a society that contains all the conditions for sustainable development in terms of equal opportunities for employment and social well-being. Currently, significant problems and dysfunctions exist as long as several European labor markets are fragmented with a strong insiders-outsiders divergence, job-polarization, high labor market slack, high in-work poverty rates especially in precarious forms of employment. In Europe as well as globally, addressing these issues is of major importance in order to ensure social sustainability, given that the permacrisis (multiple crises), along with the Mega-Trends have a clear impact on the structure of economy and labor market, industrial relations systems, and business models.MethodsThe present paper analyses the state of play of social sustainability in Europe and aims to identify specific policy responses that could offer viable solutions to old and emerging challenges in terms of social inclusion through the examination of secondary quantitative data.ResultsThe permacrisis era, along with the Mega-Trends that are taking place and seem to gradually have a clear impact on the structure of economy and labor market, substantially affecting every aspect of society, since social inequalities have the tendency to interrelate and getting reproduced.DiscussionThere is a need for knowledge-based and evidence-informed policy making, both in terms of policy design and implementation, for a true and actual sustainable (as well as inclusive) development, within momentous times.